Effects of a HAPA-based multicomponent intervention to improve self-management precursors of older adults with tuberculosis: A community-based randomised controlled trial. Issue 2 (February 2020) - Chen, Yanshu; Tan, Dixin; Xu, Yihua; Wang, Bin; Li, Xuhui; Cai, Xiaonan; Li, Mengyu; Tang, Cong; Wu, Yun; Shu, Wen; Zhang, Guoliang; Huang, Jiayu; et al.
Highlights: The HAPA-based multicomponent intervention can improve self-management precursors. Single health education is less effective than multicomponent intervention. Education and comorbidities are associated with self-management precursors. Abstract: Objective: To evaluate the effectiveness of a multicomponent intervention based on the Health Action Process Approach (HAPA) model to improve the self-management precursors of older adults with tuberculosis (TB). Methods: A cluster-randomised controlled trial was conducted. Older adults with TB in the intervention communities received HAPA-based multicomponent interventions at the beginning of treatment and in the first and sixth months after treatment initiation, and those in the control communities received health education alone. Self-management precursors were measured at baseline and 1 week after each intervention. Results: Among 262 randomized patients, 244 (93%) completed the trial. Compared with the control group, self-management precursor scores for the intervention group increased significantly over time ( β group*time = 2.92, p < 0.001) in the following 3 precursors: behaviour belief ( β group*time = 0.35, p < 0.001), behaviour plan ( β group*time = 0.72, p < 0.001), and self-efficacy ( β group*time = 1.85, p < 0.001). Education was significantly associated with behaviour belief ( β = 0.18, p < 0.05). Chronic comorbidity was significantly associated with behaviour plan ( β =−0.26, p < 0.05). Conclusion: Compared with single health education, the HAPA-based multicomponent interventions significantly improved the self-management precursor of older adults with TB. Practice implications: This HAPA-based multicomponent intervention strategy may be a promising self-management mode for the routine health care of TB patients.